Analisis Perbedaan Gender Dalam Kepuasan Kerja Pegawai Sub Bagian Keuangan Pada Dinas Cipta Karya Dan Tata Ruang Kabupaten Kutai Kartanegara - Awang Yacoub Luthman (JEMI is managed and published by the Management Study Program, Faculty of Economics and Business, Kutai Kartanegara University. Institutional legality is reflected in the ISSN number: 1411-9560 published by LIPI in 2003 as a manifestation of the comm, 2017)
Abstract:The purpose of this study was to determine and assess gender differences in job satisfaction  employees in the Finance Sub-Division of Cipta Karya and Tata Ruang Office in Kutai Kartanegara Regency. Problems seen that in achieving job satisfaction between genders in the Sub Division of Finance Office of Cipta Karya and Tata Ruang Office must not be separated from some of the factors that influence the placement, compensation, working conditions and leadership. The fact is visible in the field, employee satisfaction is not maximized. The technique of collecting data from the source to the measurement Likert scale questionnaire and interview. Data analysis technique used is chi square analysis. Total sample as many as 34 people Based on the results of the research it can be concluded that there are gender differences in job satisfaction employees of Sub Division of Finance at  Cipta Karya and Tata Ruang Office, so the hypothesis of this research is accepted and proven truth.Keywords: Gender Differences, Job Satisfaction